Virotherapy combined with anti-PD-1 transiently reshapes the tumor immune environment and induces anti-tumor immunity in a preclinical PDAC model - Veinalde, Rūta; Pidelaserra Martí, Gemma; Moulin, Coline; Tan, Chin Leng; Schäfer, Theresa E.; Kang, Na; Ball, Claudia R.; Leichsenring, Jonas; Stenzinger, Albrecht; Kaderali, Lars; Jäger, Dirk; Ungerechts, Guy; et al. (Frontiers in immunology, 2022)
IntroductionPancreatic ductal adenocarcinoma (PDAC) is largely refractory to cancer immunotherapy with PD-1 immune checkpoint blockade (ICB). Oncolytic virotherapy has been shown to synergize with ICB. In this work, we investigated the combination of anti-PD-1 and oncolytic measles vaccine in an immunocompetent transplantable PDAC mouse model.MethodsWe characterized tumor-infiltrating T cells by immunohistochemistry, flow cytometry and T cell receptor sequencing. Further, we performed gene expression profiling of tumor samples at baseline, after treatment, and when tumors progressed. Moreover, we analyzed systemic anti-tumor and anti-viral immunity.ResultsCombination treatment significantly prolonged survival compared to monotherapies. Tumor-infiltrating immune cells were increased after virotherapy. Gene expression profiling revealed a unique, but transient signature of immune activation after combination treatment. However, systemic anti-tumor immunity was induced by virotherapy and remained detectable even when tumors progressed. Anti-PD-1 treatment did not impact anti-viral immunity.DiscussionOur results indicate that combined virotherapy and ICB induces anti-tumor immunity and reshapes the tumor immune environment. However, further refinement of this approach may be required to develop its full potential and achieve durable efficacy.
Elektronische Reproduktion der Druck-Ausgabe 16. Januar 2023
Gesehen am 31.01.2023